2021
DOI: 10.1007/s00429-020-02190-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the living mouse brain neural architecture: strain-specific patterns of brain structural and functional connectivity

Abstract: Mapping the structural and functional brain connectivity fingerprints became an essential approach in neurology and experimental neuroscience because network properties can underlie behavioral phenotypes. In mouse models, revealing strain related patterns of brain wiring have a tremendous importance, since these animals are used to answer questions related to neurological or neuropsychiatric disorders. C57BL/6 and BALB/cJ inbred strains are primary "genetic backgrounds" for brain disease modelling and for test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…In this line, the first group of studies ( n = 8) compared structural and functional networks separately between wild-type and transgenic or knockout mice. Karatas et al ( 2021 ) investigated the functional and structural network differences in two commonly used mouse inbred strains: C57BL/6 and BALB/cJ. Both strains were initially developed in the early 20th century, and are since then commercially kept and distributed as genetically homogeneous inbred strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this line, the first group of studies ( n = 8) compared structural and functional networks separately between wild-type and transgenic or knockout mice. Karatas et al ( 2021 ) investigated the functional and structural network differences in two commonly used mouse inbred strains: C57BL/6 and BALB/cJ. Both strains were initially developed in the early 20th century, and are since then commercially kept and distributed as genetically homogeneous inbred strains.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, this review confirmed prior evidence of typical features of SC-FC correlation in the healthy brain (Straathof et al, 2019 ). The correlation in the diseased brain is, however, far more complex and seems to uncouple under specific conditions, i.e., the existence of interhemispheric FC despite strongly reduced SC (Vega-Pons et al, 2016 ; Karatas et al, 2021 ). From the presently available reports on different brain diseases, general pattern and intensity of SC-FC relation changes do not emerge, suggesting that the changes are disease-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted with permission from Gorges et al (2017). Karatas et al (2021) recently reported comparison of structural and functional connectivity in two healthy mouse strains (C57BL/6N and BALB/cJ) using DTI and rsfMRI. They observed inter-strain differences regarding fiber density within frontal cortices, along cortico-striatal, thalamic and midbrain pathways.…”
Section: Added Value By Combining Functional and Structural Network Readoutsmentioning
confidence: 99%
“…Nearly 150 of the connection profiles were statistically different between the C57BL/6J, DBA/2J, and CAST/EiJ lines. Recently, Karatas et al ( 2021 ) investigated strain specific patterns of brain structural and functional connectivity in C57BL/6N and BALB/cJ mouse strains. They demonstrated that structural dissimilarities were accompanied by specific FC patterns, emphasizing strain differences in frontal and basal forebrain functional networks as well as hubness characteristics.…”
Section: Network In Healthy Brainsmentioning
confidence: 99%